Tendências competitivas de atletas de basquetebol em cadeira de rodas - Luciana Erina Palma; Roberta Marostega Feck; Bhianca Conterato Patias; Fausto Friedrich (Universidade Estadual do Oeste do Paraná, 2016)
The purpose of this study was to verify competitive tendencies of wheelchair basketball athletes. For that, were researched seven individuals with physical disability, practicing of modality by one year, with mean age of thirty-five 35. The athletes answered to the Sports Orientation Questionnaire, data were analysed qualitatively, individual by individual, and results exposed descriptively. It was verified the predominant tendency between individuals was the tendency to compete (TC), then the tendency to set goals (TG) and ultimately appears to trend win (TW). These results demonstrate that the individuals like to compete independently of situation, by the pleasure inherent in sport, however, the victory is the least important factor for this team.